How to Discourse on Character Education Values in the Pullagajat Liat Tradition in Mentawai, Indonesia - Zulfa, Zulfa; Yulia, Refni; Husnita, Liza; Meldawati, Meldawati (Journal of Pragmatics and Discourse Research, 2023)
One of the traditional ritual in the Mentawai archipelago, the Tradition of Liat Pullaggajat, is in danger of dying out. This is clearly visible in the Mentawai area of South Siberut. To keep bad spirits from wreaking havoc, the villagers of Matotonan perform this annual cleansing rite. This research takes place in Matotonan Village, South Siberut District, Mentawai Islands Regency, and analyses the discourse of ritual process and the character education principles inherent in the Liat Pullagajat tradition. The researchers wanted to learn more about the significance of the ritual processions and the moral lessons taught within this culture. This research employed a qualitative strategy that combined historical analysis, ethnographic observation, and the examination of oral traditions. Methods of gathering information through direct observation, interviews, and written records. Reduction (including ritual recording), presentation, and verification of data can be achieved by processing. The results of this study found the ritual procession in carrying out the tradition of character education values contained in the Liat Pullaggajat tradition with the procession of Lia Siboitok (taddat lia), Sikebbukat sibakkat katcaila, Pasibitbit Sipitto', Lia Sikarua, Iriq toitet Iriq toitet, Lajot Simagre, Lia This ritual will be guided by the Sikerei in the villages of Matotonan, Madobag and Butui, which are in the South Siberut sub-district, Mentawai Islands district. There are nine values of character education contained in the Liat Pullagajat tradition, including religion, honesty, discipline, love of the motherland, tolerance, peace-loving, environmental care, social care, and responsibility and mutual cooperation.